Estimation of Barbodes schawanefeldii Population in the Indragiri River, Lubuk Terentang Village, Gunung Toar District, Kuantan Singingi Regency, Riau Province. - Nasution, Ali Hasyim; Sumiarsih, Eni; fauzi, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Barbodes schawanefeldii was commonly inhabit the Indragiri River. A research aims to understand the population of B. schawanefeldii in that river was conducted in July 2018. Fish was sampled everyday for 10 days, using gill nets and cast net. The population estimation was analyzed using a Leslie Method. Results shown that the initial population (No) of the fish was 446 kg and the final population (Nt) was 431 kg. The maximum value that can be exploited was 223 kg and the utilization rate was 7%. The water quality parameter shown that temperature 27-29 °C, current speed 25.9-28.5 cm/s, and depth 3.55-3.87 m. Data on water quality parameters indicate that water quality in the Indragiri River is able to support the life of B. schawanefeldii . Keywords : Leslie method, Maximum value, Utilization rate, Exploitation rate